2010
DOI: 10.5424/sjar/2010083-1284
|View full text |Cite
|
Sign up to set email alerts
|

Response of four grapevine (Vitis spp.) genotypes to direct or bicarbonate-induced iron deficiency

Abstract: In Turkey, calcareous soil conditions usually cause signif icant decreases in grape yield. Understanding the physiological responses of grapevine genotypes under such conditions would yield invaluable knowledge to recover these problems. This study was thus conducted on the comparative evaluation of the responses of four Vitis spp. materials (a cultivar, 'Alphonse Lavallee', and three rootstocks, 'Fercal', '99 R' and '1613 C'), differing in tolerance potential to direct and lime-induced chlorosis. In greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In the present study, chlorophylls decreased significantly with maturation until 45 days. Sabir et al [28] showed that the chlorophyll content of young leaves had a high correlation with iron concentration, which is an indicator of the vital role of iron in the chlorophyll content of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, chlorophylls decreased significantly with maturation until 45 days. Sabir et al [28] showed that the chlorophyll content of young leaves had a high correlation with iron concentration, which is an indicator of the vital role of iron in the chlorophyll content of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Bicarbonate (NaHCO 3 ) applications were performed when the shoots were 3-4 cm long (one week after bacteria inoculation) and was replicated one month later to increase soil pH gradually. For applications, the plants were watered with 500 mL/plant bicarbonate solution (840 g L -1 NaHCO 3 ) [Sabir et al 2010].…”
Section: Methodsmentioning
confidence: 99%
“…Studies revealed that high carbonate in soil negatively affect mineral acquisition of grapevines [Bavaresco and Poni 2003], because the availability of nutrients is restricted due to high pH due to elevated carbonate in soil [Sabir et al 2010]. About 30% of the world's area is calcareous soils with high calcium carbonate content [Sánchez-Rodríguez et al 2014], adversely affecting the leaf mineral content [Bava-resco and Poni 2003] and disturbing Fe metabolism [Sabir et al 2010]. Around the world, grapevine is generally cultivated in regions where alkaline soils with low iron availability prevail.…”
Section: Introductionmentioning
confidence: 99%
“…To establish irrigation water pH treatments for 4.0, 5.0, and 6.0, sulfuric acid (40%) was injected by hydraulic powered proportioning pumps located at the irrigation riser of each treatment row. Irrigation water samples were taken monthly and tested for pH using electrodes (14). Plots with the 3 rates of acid injection and the nontreated control were split randomly with 1 of the split plots receiving S in a controlled release form (Tiger 90CR; Tiger-Sul Products, LLC, Atmore, AL, USA) at 560 kg per ha 2 times per year.…”
Section: Acidification Field Trialsmentioning
confidence: 99%
“…In recent decades, soils under tree canopies statewide have increased in pH and bicarbonate concentrations due to irrigation with alkaline water from deep wells extending into Florida's limestone aquifers [12]. As soils become more alkaline, some nutrients are less available for uptake (e.g., Ca, Mg, Fe, Mn, Zn, and B) as observed for other crops [13,14].…”
Section: Introductionmentioning
confidence: 99%